Factores prenatales que afectan al desarrollo motor en pre-escolares de 36 a 60 meses de edad en la ciudad de Loja - Ortiz Calva, Sandra Elizabeth (2015)
Engine development children 36 to 60 months of age affected by prenatal factors which influence their future growth. This research aims to: Test performed by Denver assess and diagnose delayed motor development in children aged 36-60 months old, and a survey investigate the predisposing factors that influenced the delay in these children. It is a quantitative and qualitative descriptive study whose universe are children / as they are between 36-60 months of age and come to Outpatient Hospital Universitario Motupe city of Loja with a total number of 148 children / as to whereby the Denver Test was used, and their mothers who were applied a structured questionnaire, in order to obtain information necessary to detect causes or factors that affect or alter the normal motor development of these children the time required to perform This research was the period from May to October 2015. Upon completion of this investigation the results indicates that the total number of children / as attending outpatient at the University Hospital of Motupe city of Loja 16% had delayed gross motor development and 17% had delayed fine motor, having regard to the age of the mother during pregnancy, number of prenatal visits made, level of education of the mother, number of epic development, Keywords: motor development, Denver test, survey